Formation of complexes of astaxanthin with metal ions and their basic spectroscopic characterization - Velanová, Hana (Jihočeská univerzita, 2019)
The complexes of astaxanthin with calcium, zinc and copper were formed and characterized with UV-Vis spectroscopy. Red shifts of the absorption maxima were observed and compared with data available in the literature. Acquired complexes were subjected to HPLC analysis, however only analysis of complexes with copper was succesful and individual compounds were identified. For the same complex transient absorption spectra were measured.
Formation of complexes of astaxanthin with metal ions and their basic spectroscopic characterization